Fast optical pH manipulation and imaging - Filevich, Oscar (2012)
We describe a complete system for optical pH manipulation and imaging. The system consists of a photoactive Ruthenium complex capable of inducing a change of more than 5 pH units at the nanosecond time scale. A compatible imaging system acquires microscopic pH images at 1200 fps using a nonexpensive commercial digital camera and an LED illumination system. We use the system as a superb tool to investigate flow in Flow Injection Analysis (FIA) models.